Infective endocarditis – can we treat it more effectively? - Guzek, Aneta; Braksator, Wojciech; Gąsior, Zbigniew; Kuśmierczyk, Mariusz; Różański, Jacek; Rybicki, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2020)
Infective endocarditis (IE), despite the diagnostic and therapeutic advances, still remains a serious disease associated with high mortality and serious complications. The present guidelines of the European Cardiology Society of 2015 recommend administration of the antibiotics indicated in empirical therapy for multiple weeks and in targeted treatment often for 6–8 weeks. This is associated with a risk of adverse effects of antibiotic therapy in the form of nephro- and/or hepatotoxicity and an increased risk of infections with Clostridioides difficile, while long-term hospitalisation is associated with high non-drug costs. The recommendations developed by the Austrian Society for Infectious Diseases and Tropical Medicine list dalbavancin among the new antibiotics that may find application in the treatment of IE of staphylococcal aetiology. This antibiotic is a lipoglycopeptide antibiotic alternative to vancomycin in the treatment of Staphylococcus aureus MRSA infections, especially in a situation where the minimum inhibitory concentration for vancomycin is high but below the breakpoint. Dalbavancin has very good pharmacokinetic and pharmacodynamic properties, with a long duration of action of up to 14 days after administration of a single dose (1500 mg in a 30-minute infusion). This antibiotic is characterised by high clinical efficacy with good treatment tolerance and safety profile, without causing toxic effects in internal organs in comparison with vancomycin. In view of its safety, clinical efficacy and convenient dosing, dalbavancin may prove a useful therapeutic option in the treatment of IE.